Metallized ceramic for relay and preparation method thereof
By forming a transition layer and a metallization layer on the ceramic substrate, the difficulty and thermal stress problems of ceramics and metal materials are solved, and the bonding strength and tensile strength of the relay are significantly improved, which is suitable for new energy vehicles.
Patent Information
- Application Number
- CN202411485391.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The differences in the structure and physical and chemical properties between ceramics and metal materials make it difficult for traditional welding methods to obtain satisfactory welded joints, which are prone to thermal stress cracking, shortening the life of relays, and increasing safety hazards of new energy vehicles.
The metallized ceramics that form a transition layer on the ceramic substrate are prepared by self-propagation sintering of Ti powder, M powder, and C powder, and a metallized layer is formed thereon, and the metallized layer is prepared by magnetron sputtering method. Combining carbon ions and rare earth ions implantation modified ceramic substrates, a transition layer of high density and strength is formed to promote the bonding of the ceramic and the metallization layer.
Effectively alleviate the difference in thermal stress between the ceramic and the metallization layer, improve the bonding strength, and significantly improve the tensile strength of the metallization layer. It is suitable for the manufacturing of new energy vehicle relays.
Smart Images

Figure CN118993770B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic metallization, in particular to a metallized ceramic for relays and a preparation method thereof. Background Art
[0002] Ceramics are gaining popularity due to their low specific gravity, high hardness, excellent heat resistance, wear resistance and corrosion resistance. Ceramic relays are the core components of new energy vehicle electronic control technology, and ceramic metallization technology is one of the key processes for manufacturing relays. Among them, the most core process is to prepare a dense and uniform metallization layer on the surface of alumina ceramics to achieve brazing connection between ceramics and metal parts.
[0003] However, due to the great differences in the organizational structure and physical and chemical properties between ceramic and metal materials, it is difficult to obtain satisfactory welding joints using traditional welding methods and processes, or cracking may occur due to large thermal stress generated at the interface, which undoubtedly shortens the life of the relay and invisibly increases the safety risks of new energy vehicles. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a metallized ceramic for relays and a preparation method thereof.
[0005] The technical solutions adopted are as follows:
[0006] A metallized ceramic for a relay, comprising a ceramic substrate, a transition layer and a metallized layer;
[0007] The transition layer is prepared by self-propagating sintering using Ti powder, M powder and C powder as raw materials;
[0008] Wherein, M is a transition metal element.
[0009] The present invention also provides a method for preparing metallized ceramic for relay:
[0010] Ti powder, M powder and C powder are mixed and ball-milled, dried and pressed into a green body, the green body is placed on the surface of a ceramic substrate and put into a self-propagating sintering furnace, the self-propagating sintering furnace is heated to 400-600°C, the green body is ignited to stimulate a self-propagating sintering reaction, and after the reaction is completed, a transition layer is formed by pressurizing, and finally a metallization layer is formed on the transition layer.
[0011] Furthermore, M is any one or more combinations of Cr, Co, Ni, Cu, Fe, Zr, and Mo.
[0012] Furthermore, M is Co and Ni.
[0013] Furthermore, the molar ratio of Ti powder, Co powder, Ni powder and C powder is 1-2:0.1-0.5:1-1.5:1.
[0014] Furthermore, the ceramic matrix is pre-treated by ion implantation modification.
[0015] Furthermore, the ceramic matrix is preliminarily subjected to modification treatment by carbon ion and rare earth ion implantation.
[0016] Furthermore, the vacuum degree of the self-propagating sintering furnace is 1-5×10 -3 Pa.
[0017] Furthermore, the pressure during pressurization is 50-100 MPa, and the pressure is maintained for 10-30 minutes.
[0018] Furthermore, the metallization layer is prepared by magnetron sputtering.
[0019] Beneficial effects of the present invention:
[0020] The present invention provides a metallized ceramic for a relay and a preparation method thereof. By forming a transition layer between a ceramic substrate and a metallized layer, the bonding between the ceramic substrate and the metallized layer can be effectively promoted, the thermal stress near the interface caused by the large difference in linear expansion coefficient can be alleviated, and the bonding strength of the metallized layer can be improved.
[0021] During the self-propagating sintering reaction, Ti and C can directly react to synthesize TiC, or Ti and Ni may first form an intermediate phase, and then the intermediate phase reacts with C to generate TiC, part of Ni reacts with Ti to generate TiNi3, and the other part of Ni is dissolved in TiC, so that the prepared transition layer has more metallic properties. A small amount of Co is further added to the transition layer of the present application. Through testing, it can be concluded that the addition of Co plays a positive role in improving the bonding strength of the metallized layer. The reason may be that Co, as a traditional metal bonding phase, can improve the density of the transition layer and the bonding strength with the ceramic matrix. It is also possible that Co reacts with the ceramic matrix during the self-propagating sintering reaction, improving the interface morphology between the transition layer and the ceramic matrix, and increasing the bonding strength between the transition layer and the ceramic matrix. The specific reason needs further study;
[0022] In the present application, the ceramic matrix is pre-modified by carbon ion and rare earth ion implantation, which can activate the ceramic matrix and make the properties of the ceramic matrix and the transition layer bonding interface close to each other, thereby helping to improve the bonding strength between the two. It is also possible that the rare earth element can improve the microscopic morphology of the interface between the self-propagating sintering reaction product and the ceramic matrix, so that it has better wettability with the ceramic matrix, thereby improving the adhesion with the ceramic matrix. After the self-propagating sintering reaction is completed, the reaction product is still in a red-hot softened state. At this time, pressurization is applied to form a transition layer, which can further improve the density of the transition layer and the bonding strength between the transition layer and the ceramic matrix.
[0023] After testing, it is found that the metallized layer of the metallized ceramic prepared by the present invention has extremely high tensile strength and can be used to make new energy vehicle relays. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 Schematic diagram of the structure of the metallized ceramic prepared in Example 1;
[0025] The numbers in the figure represent:
[0026] 1-alumina ceramic substrate, 2-transition layer, 3-nickel metallization layer. DETAILED DESCRIPTION
[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0028] Embodiment 1:
[0029] A metallized ceramic for a relay, comprising an alumina ceramic substrate 1, a transition layer 2 and a nickel metallization layer 3;
[0030] Preparation method of the metallized ceramic for the above relay:
[0031] The alumina ceramic substrate 1 was washed with deionized water and ethanol in turn, dried, and fixed on an ion implanter. Carbon ions and lanthanum ions were uniformly implanted on its surface in turn. The implantation dose of carbon ions and lanthanum ions was 5×10 17 ions / cm 2 The vacuum chamber of the ion implanter is maintained at 1-1.2×10 -4Pa, under nitrogen protection, Ti powder, Co powder, Ni powder and C powder with a molar ratio of 1.5:0.1:1:1 are added to a ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, and then dried, and pressed into a green body at 5MPa, the green body is placed on the surface of an alumina ceramic substrate 1 and placed in a self-propagating sintering furnace, the self-propagating sintering furnace is heated to 550°C, and the green body is ignited by a resistance wire to stimulate the self-propagating sintering reaction, after the reaction is completed, the green body is pressurized to 50MPa from the top and maintained for 10 minutes to form a transition layer 2, and finally a nickel metallization layer 3 is formed on the transition layer 2 by magnetron sputtering, the purity of the nickel target used for magnetron sputtering is not less than 99.99%, and the pressure of argon is maintained at 2.1×10 -1 Pa, the magnetron sputtering time was 30 min, the power was 2.4 kW, the bias voltage was 30 V, and the heating temperature was 450 °C.
[0032] The metallized ceramic prepared in this embodiment is brazed with Kovar alloy. The brazing material is commercial foil AgCu28 brazing material. The brazing test is carried out in a vacuum brazing furnace. The brazing process is as follows: the brazing temperature is 840°C and the holding time is 10 min. After the holding period is completed, the specimen is cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen is tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reaches 109 MPa.
[0033] Embodiment 2:
[0034] A metallized ceramic for a relay, comprising an alumina ceramic substrate 1, a transition layer 2 and a nickel metallization layer 3;
[0035] Preparation method of the metallized ceramic for the above relay:
[0036] The alumina ceramic substrate 1 was washed with deionized water and ethanol in turn, dried, and fixed on an ion implanter. Carbon ions and lanthanum ions were uniformly implanted on its surface in turn. The implantation dose of carbon ions and lanthanum ions was 5×10 17 ions / cm 2 The vacuum chamber of the ion implanter is maintained at 1-1.2×10 -4Pa, under nitrogen protection, Ti powder, Co powder, Ni powder and C powder with a molar ratio of 1.5:0.2:1:1 are added to a ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, and then dried, and pressed into a green body at 5MPa, the green body is placed on the surface of an alumina ceramic substrate 1 and placed in a self-propagating sintering furnace, the self-propagating sintering furnace is heated to 550°C, and the green body is ignited by a resistance wire to stimulate the self-propagating sintering reaction, after the reaction is completed, the green body is pressurized to 50MPa from the top and maintained for 10 minutes to form a transition layer 2, and finally a nickel metallization layer 3 is formed on the transition layer 2 by magnetron sputtering, the purity of the nickel target used for magnetron sputtering is not less than 99.99%, and the pressure of argon is maintained at 2.1×10 -1 Pa, the magnetron sputtering time was 30 min, the power was 2.4 kW, the bias voltage was 30 V, and the heating temperature was 450 °C.
[0037] The metallized ceramic prepared in this embodiment is brazed with Kovar alloy. The brazing material is commercial foil AgCu28 brazing material. The brazing test is carried out in a vacuum brazing furnace. The brazing process is as follows: the brazing temperature is 840°C and the holding time is 10 min. After the holding period is completed, the specimen is cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen is tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reaches 121 MPa.
[0038] Embodiment 3:
[0039] A metallized ceramic for a relay, comprising an alumina ceramic substrate 1, a transition layer 2 and a nickel metallization layer 3;
[0040] Preparation method of the metallized ceramic for the above relay:
[0041] The alumina ceramic substrate 1 was washed with deionized water and ethanol in turn, dried, and fixed on an ion implanter. Carbon ions and lanthanum ions were uniformly implanted on its surface in turn. The implantation dose of carbon ions and lanthanum ions was 5×10 17 ions / cm 2 The vacuum chamber of the ion implanter is maintained at 1-1.2×10 -4Pa, under nitrogen protection, Ti powder, Co powder, Ni powder and C powder with a molar ratio of 1.5:0.3:1:1 are added to a ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, dried, and pressed into a green body at 5MPa, the green body is placed on the surface of an alumina ceramic substrate 1 and placed in a self-propagating sintering furnace, the self-propagating sintering furnace is heated to 550°C, and the green body is ignited by a resistance wire to stimulate a self-propagating sintering reaction. After the reaction is completed, the green body is pressurized to 50MPa from the top and maintained for 10 minutes to form a transition layer 2, and finally a nickel metallization layer 3 is formed on the transition layer 2 by magnetron sputtering. The purity of the nickel target used for magnetron sputtering is not less than 99.99%, and the pressure of argon is maintained at 2.1×10 -1 Pa, the magnetron sputtering time was 30 min, the power was 2.4 kW, the bias voltage was 30 V, and the heating temperature was 450 °C.
[0042] The metallized ceramic prepared in this embodiment is brazed with Kovar alloy. The brazing material is commercial foil AgCu28 brazing material. The brazing test is carried out in a vacuum brazing furnace. The brazing process is as follows: the brazing temperature is 840°C and the holding time is 10 min. After the holding period, the specimen is cooled with the furnace to obtain a specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen is tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reaches 132 MPa.
[0043] Embodiment 4:
[0044] A metallized ceramic for a relay, comprising an alumina ceramic substrate 1, a transition layer 2 and a nickel metallization layer 3;
[0045] Preparation method of the metallized ceramic for the above relay:
[0046] The alumina ceramic substrate 1 was washed with deionized water and ethanol in turn, dried, and fixed on an ion implanter. Carbon ions and lanthanum ions were uniformly implanted on its surface in turn. The implantation dose of carbon ions and lanthanum ions was 5×10 17 ions / cm 2 The vacuum chamber of the ion implanter is maintained at 1-1.2×10 -4Pa, under nitrogen protection, Ti powder, Co powder, Ni powder and C powder with a molar ratio of 1.5:0.4:1:1 are added to a ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, dried, and pressed into a green body at 5MPa, the green body is placed on the surface of an alumina ceramic substrate 1 and placed in a self-propagating sintering furnace, the self-propagating sintering furnace is heated to 550°C, and the green body is ignited by a resistance wire to stimulate the self-propagating sintering reaction. After the reaction is completed, the green body is pressurized to 50MPa from the top and maintained for 10 minutes to form a transition layer 2, and finally a nickel metallization layer 3 is formed on the transition layer 2 by magnetron sputtering. The purity of the nickel target used for magnetron sputtering is not less than 99.99%, and the pressure of argon is maintained at 2.1×10 -1 Pa, the magnetron sputtering time was 30 min, the power was 2.4 kW, the bias voltage was 30 V, and the heating temperature was 450 °C.
[0047] The metallized ceramic prepared in this embodiment is brazed with Kovar alloy. The brazing material is commercial foil AgCu28 brazing material. The brazing test is carried out in a vacuum brazing furnace. The brazing process is as follows: the brazing temperature is 840°C and the holding time is 10 min. After the holding period is completed, the specimen is cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen is tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reaches 116 MPa.
[0048] Embodiment 5:
[0049] A metallized ceramic for a relay, comprising an alumina ceramic substrate 1, a transition layer 2 and a nickel metallization layer 3;
[0050] Preparation method of the metallized ceramic for the above relay:
[0051] The alumina ceramic substrate 1 was washed with deionized water and ethanol in turn, dried, and fixed on an ion implanter. Carbon ions and lanthanum ions were uniformly implanted on its surface in turn. The implantation dose of carbon ions and lanthanum ions was 5×10 17 ions / cm 2 The vacuum chamber of the ion implanter is maintained at 1-1.2×10 -4Pa, under nitrogen protection, Ti powder, Co powder, Ni powder and C powder with a molar ratio of 1.5:0.5:1:1 are added to a ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled in a planetary ball mill for 10 hours, dried, and pressed into a green body at 5MPa, the green body is placed on the surface of an alumina ceramic substrate 1 and placed in a self-propagating sintering furnace, the self-propagating sintering furnace is heated to 550°C, and the green body is ignited by a resistance wire to stimulate a self-propagating sintering reaction. After the reaction is completed, the green body is pressurized to 50MPa from the top and maintained for 10 minutes to form a transition layer 2, and finally a nickel metallization layer 3 is formed on the transition layer 2 by magnetron sputtering. The purity of the nickel target used for magnetron sputtering is not less than 99.99%, and the pressure of argon is maintained at 2.1×10 -1 Pa, the magnetron sputtering time was 30 min, the power was 2.4 kW, the bias voltage was 30 V, and the heating temperature was 450 °C.
[0052] The metallized ceramic prepared in this embodiment is brazed with Kovar alloy. The brazing material is commercial foil AgCu28 brazing material. The brazing test is carried out in a vacuum brazing furnace. The brazing process is as follows: the brazing temperature is 840°C and the holding time is 10 min. After the holding period is completed, the specimen is cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen is tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reaches 97 MPa.
[0053] Comparative Example 1:
[0054] It is basically the same as Example 1, except that the alumina ceramic substrate 1 is not implanted with carbon ions or lanthanum ions.
[0055] The metallized ceramic prepared in this comparative example was brazed with Kovar alloy. The brazing material used was AgCu28 brazing material from commercial foil. The brazing test was carried out in a vacuum brazing furnace. The brazing process was as follows: the brazing temperature was 840°C and the holding time was 10 min. After the holding period, the specimen was cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen was tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reached 82 MPa.
[0056] Comparative Example 2:
[0057] It is basically the same as Example 1, except that the alumina ceramic substrate 1 is only implanted with carbon ions but not with lanthanum ions.
[0058] The metallized ceramic prepared in this comparative example was brazed with Kovar alloy. The brazing material used was AgCu28 brazing material from commercial foil. The brazing test was carried out in a vacuum brazing furnace. The brazing process was as follows: the brazing temperature was 840°C and the holding time was 10 min. After the holding period, the specimen was cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen was tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reached 96 MPa.
[0059] Comparative Example 3:
[0060] It is basically the same as Example 1, except that the alumina ceramic substrate 1 is not implanted with carbon ions but only implanted with lanthanum ions.
[0061] The metallized ceramic prepared in this comparative example was brazed with Kovar alloy. The brazing material used was commercial foil AgCu28 brazing material. The brazing test was carried out in a vacuum brazing furnace. The brazing process was as follows: the brazing temperature was 840°C and the holding time was 10 min. After the holding period, the specimen was cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen was tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reached 100 MPa.
[0062] Comparative Example 4:
[0063] It is basically the same as Example 1, except that Co powder is not added.
[0064] The metallized ceramic prepared in this comparative example was brazed with Kovar alloy. The brazing material used was AgCu28 brazing material from commercial foil. The brazing test was carried out in a vacuum brazing furnace. The brazing process was as follows: the brazing temperature was 840°C and the holding time was 10 min. After the holding period, the specimen was cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen was tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reached 88 MPa.
[0065] Comparative Example 5:
[0066] It is basically the same as Example 1, except that no pressure is applied after the self-propagating sintering reaction is completed.
[0067] The metallized ceramic prepared in this comparative example was brazed with Kovar alloy. The brazing material used was commercial foil AgCu28 brazing material. The brazing test was carried out in a vacuum brazing furnace. The brazing process was as follows: the brazing temperature was 840°C and the holding time was 10 min. After the holding period, the specimen was cooled with the furnace to obtain the specimen. The tensile strength of the nickel metallization layer 3 on the surface of the specimen was tested with reference to SJ / T3326 2016 "Test Method for Tensile Strength of Ceramic Metal Seals". The tensile strength of the nickel metallization layer 3 reached 93 MPa.
[0068] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A metallized ceramic for a relay, characterized in that: It includes a ceramic substrate, a transition layer and a metallization layer; The ceramic substrate is an alumina ceramic substrate, and the metallization layer is a nickel metallization layer; The ceramic matrix is modified by carbon ion and lanthanum ion implantation; The transition layer is prepared by self-propagating sintering using Ti powder, M powder and C powder as raw materials; Wherein, M is Co and Ni; The molar ratio of Ti powder, Co powder, Ni powder and C powder is 1-2:0.1-0.5:1-1.5:
1.
2. A method for preparing the metallized ceramic for relay according to claim 1, characterized in that: Ti powder, M powder and C powder are mixed and ball-milled, dried and pressed into a green body, the green body is placed on the surface of a ceramic substrate and put into a self-propagating sintering furnace, the self-propagating sintering furnace is heated to 400-600°C, the green body is ignited to stimulate a self-propagating sintering reaction, and after the reaction is completed, a transition layer is formed by pressurizing, and finally a metallization layer is formed on the transition layer.
3. The method for preparing the metallized ceramic for relay according to claim 2, characterized in that: The vacuum degree of the self-propagating sintering furnace is 1-5×10 -3 Pa.
4. The method for preparing the metallized ceramic for relay according to claim 2, characterized in that: The pressure during pressurization is 50-100MPa, and the pressure is maintained for 10-30min.
5. The method for preparing the metallized ceramic for relay according to claim 2, characterized in that: The metallization layer is prepared by magnetron sputtering.
Citation Information
Patent Citations
Piezoelectric ceramic composite material and preparation method and application thereof
CN113929487A
Welding using metal-ceramic composites
US4738389A